2017
DOI: 10.1038/ncb3598
|View full text |Cite|
|
Sign up to set email alerts
|

ZSCAN10 expression corrects the genomic instability of iPSCs from aged donors

Abstract: Induced pluripotent stem cells (iPSCs), which are used to produce transplantable tissues, may particularly benefit older patients, who are more likely to suffer from degenerative diseases. However, iPSCs generated from aged donors (A-iPSCs) exhibit higher genomic instability, defects in apoptosis and a blunted DNA damage response compared with iPSCs generated from younger donors. We demonstrated that A-iPSCs exhibit excessive glutathione-mediated reactive oxygen species (ROS) scavenging activity, which blocks … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
38
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(38 citation statements)
references
References 64 publications
0
38
0
Order By: Relevance
“…Comparative analyses of rodent and primate EPI defines conserved core pluripotency factors, in addition to POU5F1, SOX2 and NANOG. These include TFCP2L1 (Martello et al, 2013;Ye et al, 2013), ZSCAN10, shown to promote genomic stability in mouse embryonic stem cells (Skamagki et al, 2017), ZNF296, a component of heterochromatin (Matsuura et al, 2017) reported to enhance reprogramming efficiency (Fischedick et al, 2012) and interact with KLF4 (Fujii et al, 2013), ZFP36L1, a zinc-finger RNA-binding protein attenuating protein synthesis (Stoecklin et al, 2002) and…”
Section: Discussionmentioning
confidence: 99%
“…Comparative analyses of rodent and primate EPI defines conserved core pluripotency factors, in addition to POU5F1, SOX2 and NANOG. These include TFCP2L1 (Martello et al, 2013;Ye et al, 2013), ZSCAN10, shown to promote genomic stability in mouse embryonic stem cells (Skamagki et al, 2017), ZNF296, a component of heterochromatin (Matsuura et al, 2017) reported to enhance reprogramming efficiency (Fischedick et al, 2012) and interact with KLF4 (Fujii et al, 2013), ZFP36L1, a zinc-finger RNA-binding protein attenuating protein synthesis (Stoecklin et al, 2002) and…”
Section: Discussionmentioning
confidence: 99%
“…Although ROS is detrimental to genomic stability, certain level of ROS is also essential to signal cellular stress and to induce DNA damage response (Skamagki et al 2017). ROS can directly oxidize ATM to activate this kinase and elicit ATM-mediated DNA damage response (Guo et al 2010).…”
Section: Glucose Metabolism In Pscsmentioning
confidence: 99%
“…To maintain the homeostasis between ROS and glutathione, PSCs express specific transcription factor Zscan10, which binds to the promoter of glutathione synthetase (GSS) and suppresses its transcription. Inadequate induction of Zscan10 in iPSCs will result in the excessive expression of GSS and the disruption of homeostasis between ROS and glutathione, leading to the genomic instability (Skamagki et al 2017).…”
Section: Glucose Metabolism In Pscsmentioning
confidence: 99%
“…After constricted migration, nuclear oxidative stress is ~30% higher based on labeling by a redox dye ( Fig.3A). We therefore added a membrane-permeable antioxidant, glutathione, as a reduced monoethyl ester (GSH-MEE) that reduces H2O2-induced DNA damage in 2D cultures (Fig.3A, S2A); GSH-MEE has likewise been shown to reduce oxidative stress and genomic instability in pluripotent stem cells in 2D cultures (Skamagki et al, 2017). Partial rescue of DNA damage by GSH-MEE does not affect migrated cell numbers or nuclear blebs ( Fig.3B,C).…”
Section: Overexpressed Dna Repair Factors or Added Antioxidant Rescuementioning
confidence: 99%